A Comprehensive Philippine Government Strategy on the Competitiveness of the Services Sector - Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2015)
There is now broad consensus that the Philippines should aim to have a globally competitive services sector. Applying Porter's framework on creating national competitive advantage (the diamond), this paper presents a comprehensive government strategy recognizing that it has an important albeit partial role in attaining the national vision for services. Moreover, it emphasizes that the proper role for government policy toward industry is to stimulate dynamism and upgrading.The strategy covers four interdependent sets of policies that influence national advantage, namely, policies to enhance a country's position in the factors of production relevant to the industry, policies that raise the quality of domestic demand necessary for constant upgrading, policies to ensure the presence of supporting and related industries, and policies to influence competitive behavior through firm strategy, structure, and rivalry.
Keywords: 330; Philippines; services; competitive advantage; Porter's diamond